A CFD‐DEM approach to model the orientation and distribution of non‐spherical fibers in fresh concrete. Issue 1 (17th December 2018) - Gerland, Florian; Schomberg, Thomas; Wünsch, Olaf
Abstract: Modern high performance concretes are reinforced by fibers to cast complex parts without reinforcing bars. The orientation and distribution of fibers influence the properties of the final solid and the flow properties of fresh concrete. Therefore it is important to predict the casting process adequately. A promising method for this is CFD‐DEM. The suspending phase is described as a continuum and can be solved using suitable methods such as Finite Volume Method (FVM). The suspended particles are modeled as rigid bodies and simulated using the Discrete Element Method (DEM). This work is based on the CFDEM® engine which uses OpenFOAM® for the suspending phase and LIGGGHTS® for the particles. The modeling of fluid‐particle interaction forces and the momentum coupling between the phases is of outstanding relevance for the applicability of this method. Therefore the influence of particle to mesh size ratio on the accuracy of the coupling as well as the mapping of particle quantities to Eulerian fields is investigated.